2004
DOI: 10.1080/09540120410001665358
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activities and social relationships of people with HIV in Japan

Abstract: Sixty-one Japanese with sexually transmitted HIV were investigated to clarify the state of, and difficulties in, their sexual activities and social relationships. The study revealed the following difficulties in social relationships due to HIV infection. Thirty-one per cent had experienced discrimination or breach of confidentiality. Self-restriction due to anxiety over discrimination was observed in approximately 90%, and the self-restriction score tended to be higher in those who were not employed, those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
4
19
0
Order By: Relevance
“…Bouhnik et al (2008) found that 33% of respondents declared having sexual difficulties. In addition, another study found that as much as 60% of HIV-positive respondents declared being dissatisfied with their sexual lives (Inoue et al, 2004). Some limitations must be highlighted before discussing our results.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Bouhnik et al (2008) found that 33% of respondents declared having sexual difficulties. In addition, another study found that as much as 60% of HIV-positive respondents declared being dissatisfied with their sexual lives (Inoue et al, 2004). Some limitations must be highlighted before discussing our results.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, it is not surprising that there exists a relationship between the experience of stigma and discrimination and the psychosocial aspects of PLWHA's quality of life (Pre´au et al, 2007;Subramanian, Gupte, Dorairaj, Periannan, & Mathai, 2009). However, there is a lack of literature regarding sexual satisfaction among PLWHA (Inoue, Yamazaki, Seki, Wakabayashi, & Kihara, 2004;Lambert, Keegan, & Petrak, 2005) and, to our knowledge, its association with the HIV-related stigma and discrimination has been barely studied (Bouhnik et al, 2008). *Corresponding author.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…11 The preliminary survey was carried out in September to November 2000, and the questionnaire used in this study was prepared on the basis of the results. 12 Participants in the study were recruited from November 2002 to April 2003 at four major hospitals in Japan (two in Tokyo, one in Osaka, and one in a northern area of Japan), relatively experienced in HIV treatment. Criteria for the participants were as follows: (1) Japanese, with sexually transmitted HIV and (2) those who visited the hospitals regularly.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…A considerable number of HIV patients in Japan have experienced discrimination or breach of confidentiality and they feel insufficiency of social and economical supports. 22 Patients with mycobacterial infection used to be discriminated, but the prejudice toward the patients declines. The medical, social and economic backgrounds of HIV patients in Japan differ considerably from those in regions such as North America, Europe and Africa.…”
Section: Introductionmentioning
confidence: 99%